Implementasi Pengelolaan Keuangan Desa (Studi Kasus Desa Rawa Burung, Kabupaten Tangerang, Banten) - Amrie Firmansyah (Universitas Muhammadiyah Prof. DR HAMKA., 2018)
Abstract This study aims to determine the implementation of village financial management covering the phases of planning, implementation, administration, reporting, and accountability. The method used in this study is a descriptive qualitative and using data research technique with an in-depth interview, observation, and documentation. Rawa Burung Village is used in this study because it has a location close to DKI Jakarta Province which is expected to have competent s in village financial management. Informants in this research are village government officers who understand the village financial management cycles. The results of this study concluded that the village financial management, in general, has been conducted accountably and transparently in accordance with the applicable rules. However, the implementation of village financial management is dominated by the head of the village government section, not the village treasurer who is supposed to the village finance management functions. This is due to the lack of standard operating procedures for village financial management, clear job description, and qualification of job competence. The low salaries in the village administration resulted in the reluctance of people to work in the village government. In addition, Rawa Burung Village does not have officers with an educational background in accounting. Keywords: village financial management, accountable, transparent